If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8p-6(p+5)=-2(2p-3)
We move all terms to the left:
8p-6(p+5)-(-2(2p-3))=0
We multiply parentheses
8p-6p-(-2(2p-3))-30=0
We calculate terms in parentheses: -(-2(2p-3)), so:We add all the numbers together, and all the variables
-2(2p-3)
We multiply parentheses
-4p+6
Back to the equation:
-(-4p+6)
2p-(-4p+6)-30=0
We get rid of parentheses
2p+4p-6-30=0
We add all the numbers together, and all the variables
6p-36=0
We move all terms containing p to the left, all other terms to the right
6p=36
p=36/6
p=6
| 2(x-1)+8=6(2x-4 | | 2(2w+4)=3/4(24-8w) | | 5y+2+3y+5=10y-9 | | 7.25y=72.5 | | 6m=9÷2 | | 2(r+13)=70 | | (2x+5)=29 | | (2x+5)+29=180 | | -6(2x-4)+10=2 | | d-27+7=6 | | 82+7n=68 | | 16t-4(6t-5)=12 | | 13r=3/6 | | 26-12x=19+2x | | 6(-3x-4)+15=9 | | 8/3m-2=2/3m-12 | | 8^2x=2(x+1) | | 15x+4(2x-2)+17=0 | | k-87+9=1 | | 3=2(x-1) | | -4(x+3)=72 | | 2a-19.9=a+2.1 | | 3=2(x-1 | | v-8=4v+16 | | |2+3x|-9=7 | | (1)/(2)x-18=2 | | 8(c+97)=-64 | | 8^2x=2^(x+1) | | 2m+3(m+5)=30 | | -2=6p-6+4 | | 2/3-4x+7/2=-9x=5/6 | | 2(4x+10)=8x+2 |